SOAL MODEL PISA KONTEN UNCERTAINTY & DATA UNTUK MENUNJANG LITERASI MATEMATIS PESERTA DIDIK SMP/MTS - Wisnu Siwi Satiti; Mei Listikawati (LPPM Universitas KH.A.Wahab Hasbullah Jombang, 2021)
There are some important skills to be mastered in the 21st century, such as basic literacy, competence and character. One of the basic literacy required is mathematical literacy. Mathematical literacy is an individual's capacity to use mathematical reasoning, formulate, implement and interpret mathematics with the aim of solving problems in various real-world contexts. The type of mathematical activity that is able to accommodate mathematical literacy is PISA-like mathematics-problems. However, several previous studies have shown that many Indonesian students have difficulty in solving PISA-like mathematics-problems, especially on Uncertainty and Data content. One factor that causes this is that many students do not know or lack practice in solving PISA-like mathematics-problems. Therefore, it is necessary to increase the use of PISA-like mathematics-problems as a mathematics-learning-activity in schools. Thus, in this study, the PISA-like mathematics-problems of Uncertainty and Data content was developed. The product developed is used as a mathematical activity in learning at school as an effort to support students' mathematical literacy. This study uses Research and Development (R&D) method with the ADDIE model. The product trial results shows that the product developed is valid and appropriate to support students' mathematical literacy. In addition, the product received good responses from students.